Evaluating the teaching competencies of female Sharia science teachers at the secondary stage in Riyadh in the light of sustainable professional development - El-Metarey, Mona Shabab (Journal of Educational and Psychological Sciences, 2022)
The study aimed to assess the teaching competencies of female teachers of Sharia sciences at the secondary stage in Riyadh in the light of sustainable professional development. The study was applied to a sample of (59) secondary school teachers. The study concluded: that the degree of availability of teaching competencies obtained an overall average (1.37 out of 3), meaning a (weak) degree of availability and at the level of the axes; The competencies related to educational technologies got the highest average (1.47), followed by the planning competencies with an average of (1.41), thirdly, the classroom management competencies with an average of (1.38), then the lesson implementation competencies with an average of (1.33), and finally the evaluation competencies with an average of (1.28), all with a degree of availability (weak). There is a statistically significant difference due to the experience variable in the first axis in favor of those with less than five years and more than ten years of experience and the card as a whole in favor of those with less than five years of experience, and the absence of a statistically significant difference due to the experience variable in the rest of the second, third, fourth and fifth axes. And the absence of a statistically significant difference attributed to the educational qualification variable in the card and card axes as a whole. Based on the results, the researcher presented a number of recommendations and proposals to improve the teaching competencies of female teachers of Sharia sciences in the secondary stage in the light of sustainable professional development in the city of Riyadh and the whole of the Kingdom.